Formulation and characterisation of banana rachis derived composites and its application in adsorption of dyes - Phungo, Matodzi (My University, 2020)
Adsorption of Coomassie brilliant blue (CBB G-250) from aqueous solutions on the adsorbents chitosan, alpha cellulose, banana rachis fibre, banana rachis fibre/chitosan composite, alpha cellulose/chitosan composite, and activated carbon were studied experimentally. The removal efficiency of the adsorbents was also tested using a concentration of dye from 50 to 800 mg/l. The absorbed amount increases as the adsorbents mass increases (1, 1.5, 2, 2.5, and 3 g/l) from alpha cellulose (9.4 to 50%), chitosan (15.6 to 56.3%), banana rachis fibre (21.9 to 65.5%), alpha cellulose/chitosan composite (6.3% to 84.4%), activated carbon (31.6 to 84.4%), and banana rachis fibre/chitosan composite (37.5% to 93.8%), for the initial concentration (50 mg/l) after 80 minutes. The absorbed amount increases as the adsorbents mass increases from banana rachis fibre (6.6 to 19.5%), alpha cellulose (5.3 to 28.1%), chitosan (21.0 to 33.7%), alpha cellulose/chitosan composite (38.2 to 44.8%), banana rachis fibre/chitosan composite (45.3 to 51.2%), and activated carbon (66.8 to 79.8%), for the high concentration (800 mg/l) after 80 minutes. Two isotherm models namely Freundlich and Langmuir models were tested. The equilibrium data for alpha cellulose/chitosan composite, activated carbon, alpha cellulose, banana rachis fibre/chitosan composite, banana rachis fibre, and chitosan fitted well to the Langmuir model, correlation coefficient R2 (0.9999, 0.9984, 0.998, 0.994, 0.9661, and 0.9474 respectively) were bigger than the corresponding Freundlich correlation coefficient R2. Composites as well as components of composites were further characterized by x-ray diffraction (XRD). The (%) CIXRD of chitosan, alpha cellulose/chitosan composite, alpha cellulose, banana rachis fibre/chitosan composite, and banana rachis fibre readings values in this study ranges from 94.28%, 91.54%, 82.75%, 60.77%, and 37.69%, respectively. The present study results suggest the possible use of a waste such as banana rachis fibre waste combined with chitosan for the development of a new cheap and efficient adsorbent that could be used in dyes removal from wastewater. Adsorption of Coomassie brilliant blue (CBB G-250) from aqueous solutions was absorbed better by banana rachis fibre/chitosan composite, followed by activated carbon and then the banana rachis fibre.
MSc (Biochemistry)
Department of Biochemistry
Keywords: Adsorption; UCTD; Banana rachis fibre; Composites; ATR-IR; X-ray diffraction; Isotherm; Coomassie Brilliant Blue